1T metallic vanadium disulfide hybridized with MXene and functionalized‐MWCNT as a remarkable electrode for high power density asymmetric supercapacitor applications. (23rd August 2022) - Sharma, Aditya; Rout, Chandra Sekhar
Summary: The present work explores the 1 T Metallic Vanadium disulfide/MXene/functionalized multiwalled carbon nanotubes (1 T‐VS2 ‐MX‐CNT) ternary hybrid prepared by a facile hydrothermal method for high‐performance asymmetric supercapacitor applications. The systematic studies of the VS2 ‐MX‐CNT ternary hybrid structure reveal an increase in interlayer spacing from 13.45 to 13.81 Å obtained from the x‐ray diffraction patterns, depending on the ratio of precursors used for the synthesis. Furthermore, The optimized 1 T Metallic Vanadium disulfide/MXene/functionalized MWCNTs with 50 mg (VS2 ‐MX‐CNT‐50) ternary hybrid attained the maximum specific capacitance of 505 F/g at 0.2 A/g. The VS2 nanosheets not only restrict the MXene layers from re‐stacking but also act as a pore space for electron transfer. The electrochemical properties of the VS2 ‐MX‐CNT ternary hybrid was enhanced even further by depositing functionalized MWCNTs which helps to make a conductive channel for better ion transport. The detailed analysis demonstrates that capacitive contributions dominate diffusive contributions in the overall collective charge storage for the best performing VS2 ‐MX‐CNT‐50 ternary hybrid material. Furthermore, the VS2 ‐MX‐CNT‐50 // functionalized MWCNT (MWCNT) asymmetric supercapacitor cell was also designed to achieve an extraordinary energy density of 59.85 Wh kg −1 and maximum power density of 7303.72 W kg −1 along with a wide 1.7 V potential window. Hence, VS2 ‐MX‐CNT‐50 // MWCNT‐based asymmetric supercapacitor devices emerge as high power density energy storage devices for flexible and wearable device applications. Abstract : A remarkable combination of 1T metallic vanadium disulfide hybridized with Mxene and functionalized MWCNTs for high energy and power density asymmetric supercapacitor applications.